The Role of the Green Economy in Promoting Sustainable Growth in Indonesia - Dodi Arif; Gregorius Paulus Tahu; Septimus Adrianus Mali; Aldian Yusup; Farhan Hermawan (Mandalika Institute, 2026)
This study examines the role of the green economy in promoting sustainable economic growth in Indonesia. Rapid economic development has improved welfare but also caused environmental degradation, resource depletion, and increased carbon emissions, highlighting the need for a more sustainable development approach. Therefore, this study aims to analyze how the green economy contributes to sustainable growth and identify key factors influencing its implementation. The research employs a qualitative approach using a literature review method, collecting secondary data from scholarly articles, books, and official reports. Data are analyzed using descriptive and thematic analysis to identify patterns and relationships. The findings indicate that the green economy plays a significant role in enhancing resource efficiency, encouraging environmentally friendly technological innovation, creating green jobs, and reducing environmental impacts. It also supports renewable energy development and circular economy practices. However, its implementation is influenced by factors such as government policy, green investment, human resource capacity, and technological advancement, with regulatory support being the most critical. Overall, the green economy is an effective strategy for balancing economic growth and environmental sustainability in Indonesia.